PENGARUH DIGITALISASI PRODUK, BRAND IMAGE DAN LOKASI TERHADAP INTENSI GENERASI MILLENIAL MENGGUNAKAN JASA KEUANGAN DI LEMBAGA KEUANGAN SYARIAH (Studi Kasus Mahasiswa Angkatan 2015 STAIM Nglawak Kertosono) - Khasanah, Iva Hidayatul (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aimed to determine the effect of Digitizing Products, Brand Image, and Location on the Intention of Millennials Using Financial Services in Islamic Financial Institutions for Students of STAI Miftahul ‘Ula Nglawak Kertosono Nganjuk Group 2015. The research methodology used was a quantitative approach. This study had 70 students as the population and used 59 students as the sample of STAI Miftahul ‘Ula Nganjuk group 2015. The data collection technique used was questionnaire and documentation. The validity test of the instrument used the Product Moment (Person) correlation, while the reliability test used Cronbach Alpha. The data analysis technique used was multiple linear regression analysis using SPSS 25. The results showed that: (1) there was a positive amounting 0,269 between effect of product digitalization on millennial generations' intention to use financial services in Islamic financial institutions with a significant level of 0.013 <0.05; (2) there was a positive amounting 0,265 between effect of brand image on millennial generations' intention to use financial services in sharia financial institutions with a significant level of 0.014 <0.05; (3) there was a positive amounting 0,205 between influence on location to millennial generations' intention to use financial services in Islamic financial institutions with a significant level of 0.008 <0.05; (4) There was the influence of Digitizing products, Brand Image, and Location simultaneously to millennial generations intention to use financial services at Islamic institutions at a significance level of 0,000 <0.05. So the conclution, Digitizing products, Brand Image, and Location influential to millenial generations intention to use financial services at Islamic institution.